Electronic Medical Record Officers' Perception of Ease of Filling, Security and Legal Evidence - Jamal Nasir Husni; Sumijatun Sumijatun; Tina Rosa (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hospitals using electronic medical records (EMR) face a number of challenges, such as poor system functionality, a lack of computer skills among medical personnel, and concerns about data security and privacy. Hospital adoption of these systems is also often hampered by high implementation costs. The purpose of this study was to determine how staff at Bhayangkara Level III Hospital in Banda Aceh, who work with electronic medical records, perceive security, ease of entry, and legal evidence. A cross-sectional study design was used in conjunction with quantitative research. Using a total sampling method, 36 EMR staff were sampled. An instrument developed based on existing literature was used to collect data. Descriptive and inferential analyses were performed on the data. The study findings partially indicate a very strong relationship between perceptions of EMR and ease of data entry (P = 0.0001) with a coefficient of determination (R2) of 0.992; a very strong relationship between perceptions of EMR and data security (P = 0.0001) with a coefficient of determination (R2) of 0.922; and a very strong relationship between RME perceptions and legal evidence (P = 0.0001) with a coefficient of determination (R2) of 0.369. Based on the research findings, RME staff perceptions are strongly correlated with data security, ease of data entry, and legal evidence.